Reduction of Resistivity and Haze in Two Coating Layer of Indium Tin Oxide Doped Phosphorous on Glass - Salar Amoli, H.; Barker, J. (Asian Journal of Chemistry, 2010)
In this research work, transparent conductive films produced by a series of steps comprising two coating layer having low haze of less than 3 %. The first coating layer obtained by dissolving indium compound and a tin compound in an organic, then coated on a glass substrate. The second was a coated substrate with conductive indium tin oxide and a phosphorous film. A calcinations step was carried out in which the coated substrate is calcinated at a temperature of 400 ºC or higher. Two tin layers causes excellent properties as strong adhesive strength to a subs-trate, increasing transmittance and low sheet resistance comparing to single indium-thin oxide layer. A series of two layer film thickness have been deposited on glass substrate and the effect of film thickness on the structural, electronically and optical properties have been investigated. The total film thickness is 500 nm to 50 μm. The transmittance of two layer coating is more than 83 % at a wavelength of 510 nm and the lowest resistance of 138 W sq-1 obtained.